Government Capability in Encouraging Sustainable Innovation: A Case Study of the Makassar City Tourism Alley Program - Nur Fadillah Rianti Handayai Mardin; M. Thahir Haning; Suryadi Lambali (Journal La Sociale, 2023)
This study aims to analyze the innovation capacity of the Lorong Wisata Makassar program based on the innovation capability model developed by Lawson & Samson (2001). By analyzing the seven elements of innovation capability, namely: vision and strategy, utilization of bases and competencies, organizational intelligence, management of creativity and ideas, structure and organization, culture and climate and technology management. The type of research used is to use an exprolative qualitative approach to analyze and prorelate in depth related to the phenomena that occur in research. Data collection techniques i.e., observation, in-depth interviews, documentation. The results showed that in element the Vision and Strategy have been implemented optimally because the program has been able to improve the economy of the hallway community. Base utilization and competence have not been achieved due to budget constraints in the utilization of hallways. Organizational intelligence has run well as seen from the government's ability to change people's mindset. Management of creativity and ideas has been carried out optimally, supported by the ability of the Makassar City government to provide stimulant assistance to the community through synergy between SKPD. The organizational structure and system have been implemented optimally, because the Makassar City government has been able to monitor the development and monitoring of the hallway regularly. The culture and climate of implementation have not been able to be optimal, this is due to the development of Lorong Wisata which is continuously established by the government, while on the other hand there are still many abandoned alleys.